Prescribed fire is unlikely to reduce net PM 2.5 emissions in most locations - Mark R. Kreider; Shawn P. Urbanski; Joseph Fargione (Proceedings of the National Academy of Sciences, 2026)
Wildfire smoke poses a growing global health risk, largely from fine particulate matter (PM 2.5 ) emissions. Prescribed fires, which are critical for maintaining resilient forests in many locations, can also reduce wildfire emissions in treated areas that later burn. However, prescribed fires also produce smoke, creating a tradeoff in their net impact on PM 2.5 emissions. We develop a mathematical framework showing that, under most current conditions globally, prescribed fire emissions are rarely offset by reduced wildfire emissions and therefore increase PM 2.5 emissions overall. An analysis of 73 prior study sites reveals that reported net emission reductions are often based on unrealistic assumptions, for example that all treatments are subsequently encountered by wildfire during their effective lifespan. Using empirically based estimates of expected encounter rates, prescribed fire increases net emissions at 99% of sites, with a median 10-year increase of 210% (IQR: 70 to 475%), and only 0.06 tons of wildfire emissions avoided per ton of prescribed fire emissions (IQR: 0.03 to 0.15). However, prescribed fires are intentionally conducted under favorable meteorological conditions, allowing smoke to disperse more safely than during wildfires. Thus, whether prescribed burning can reduce health risks while increasing emissions—and whether its emissions impact can be lowered beyond current practice—is a critical area for future study. Regardless, prescribed fires have multiple objectives and benefits; they remain essential for forest management and hazard reduction.